2005
DOI: 10.1007/s00429-005-0013-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of chemokine receptor CXCR4 during chick embryo development

Abstract: The chemokine receptor CXCR4 plays a decisive role in physiological cell migration both in developmental processes and adult tissues; it has also been implicated in metastasis formation of different human cancers (Balkwill 2004) and in HIV pathogenesis (Murdoch 2000). Here we present the expression pattern of this important chemokine receptor CXCR4 in the chick embryo. A dynamic expression pattern can be detected beginning as early as the gastrulation stages until the observed stage of HH28. During gastrulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 33 publications
3
44
0
Order By: Relevance
“…2 I). These expression patterns are summarized in Figure 2C and are supported by other recent in situ hybridization analyses in chick (Yusuf et al, 2005) showing strong expression of CXCR4 in developing SGs but absence of expression in immature DRGs. Based on these data, we hypothesized SDF-1 expression may guide SG precursors toward the dorsal aorta.…”
Section: Cxcr4 Is Expressed By a Subset Of Trunk Nccssupporting
confidence: 86%
“…2 I). These expression patterns are summarized in Figure 2C and are supported by other recent in situ hybridization analyses in chick (Yusuf et al, 2005) showing strong expression of CXCR4 in developing SGs but absence of expression in immature DRGs. Based on these data, we hypothesized SDF-1 expression may guide SG precursors toward the dorsal aorta.…”
Section: Cxcr4 Is Expressed By a Subset Of Trunk Nccssupporting
confidence: 86%
“…We have previously reported the expression pattern of CXCR4 in the developing chick embryo (Yusuf et al, 2005). In our present work, we noticed that complementarity exists between the expression pattern of SDF-1 and CXCR4 during several stages of embryonic development.…”
Section: Discussionsupporting
confidence: 65%
“…In mice, the expression patterns of stromal cell-derived factor-1 and its receptor are also particularly noticeable in the developing cardiac, vascular and craniofacial system during organogenesis (McGrath et al, 1999). CXCR4 receptor is widely expressed in various tissues of the developing chick embryo such as in the ventral forgut portal, developing somites, tailbud, Wolffian duct, the lateral plate mesoderm and developing blood vessels (Yusuf et al, 2005). In our study we documented the normal expression pattern of CXCL12 (SDF-1) in chick embryos and we observed that SDF-1 is widely expressed in most of the embryonic tissues during development such as in the ectoderm, the sclerotome, the intersomitic spaces and the mesenchyme of the developing limbs.…”
Section: B C D Ementioning
confidence: 99%
“…Seen in this light the extensive role for chemokine signaling in the control of leukocyte trafficking can be thought of as an evolutionary development of this original function. Consistent with this idea, it has been demonstrated that of all chemokines and chemokine receptors, SDF-1 and CXCR4 are the most widely expressed during the development of the embryo (Knaut et al, 2005;Knaut et al, 2003;McGrath et al, 1999;Moepps et al, 2000;Rehimi et al, 2008;Tissir et al, 2004;Yusuf et al, 2005). Moreover, the expression patterns for both SDF-1 and CXCR4 are highly dynamic consistent with the possibility that they have shifting developmental roles in the formation of many different tissues.…”
Section: The Chemokine Familymentioning
confidence: 56%